Gut and intraocular fluid dysbiosis in people with type 2 diabetes-related retinopathy in India: A case for further research - Taraprasad Das; Brijesh Takkar; Shalem R Padakandala; Sisinthy Shivaji (Indian Journal of Ophthalmology)
Purpose: To explore the relationship between gut microbiome, gut mycobiome, and intraocular (aqueous humor) microbiome dysbiosis in people with type 2 diabetes (T2DM) and diabetic retinopathy (DR). Design: Multiple case-control studies. Methods: We evaluated three groups of people: healthy controls (HC), people with T2DM without retinopathy, and those with DR. The study samples included fecal matter (30–50 g) and aqueous humor (0.05–0.1 mL). After amplicon sequencing, we analyzed microbiome profiles (V3–V4 region of bacterial 16S rRNA gene) and mycobiome (ITS2 region of fungal rRNA gene). The main outcome measures were relative abundance, α and β diversity, and dysbiotic bacteria and fungi, analyzed based on the inferred functions of the taxa. Results: We recruited 82 people for gut microbiome (30 HC, 24 DM, and 28 DR); 75 people for gut mycobiome (30 HC, 21 DM, and 24 DR); and 12 people for aqueous humor microbiome (4 each HC, DM, and DR) studies. Generally, there was an increased abundance of pro-inflammatory and pathogenic microorganisms and a decreased abundance of anti-inflammatory and probiotic microorganisms. The differences were higher between HC and DM/DR than between DM and DR. In aqueous humor, there was a wider separation in microbiome profiles of people with DR than their gut microbiome. Conclusion: The gut and aqueous humor microbiota of people with diabetes and DR may differ from those without diabetes. Given these unique observations in individuals living in one region of India, further research involving people from different regions is required to identify indices for possible regional or global use.